2018
DOI: 10.1111/ene.13826
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of genetic biomarkers in isocitrate dehydrogenase‐wild‐type lower‐grade glioma: the need to further stratify this tumor entity – a meta‐analysis

Abstract: The clinical outcomes of isocitrate dehydrogenase‐wild‐type (IDH‐wt) lower‐grade glioma (LGG) have been the subject of debate for some time. In this meta‐analysis, we aimed to assess the prognostic values of several known genetic markers (e.g. TERT promoter mutation, H3F3A mutation, CDKN2A loss) in this tumor group. Four electronic databases, including PubMed, Scopus, Web of Science and Virtual Health Library, were searched for relevant articles. Pooled hazard ratio (HR) and corresponding 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…34 A more recent meta-analysis by Vuong et al also demonstrated a propensity for IDH-wildtype low-grade gliomas to have a poor prognosis when associated with TERT promoter mutations, EGFR amplifications, and H3F3A mutations, whereas ATRX mutation, 7q gain/10q loss, and CDKN loss did not influence prognosis. 54 Thus, there is not enough evidence that IDH status alone should dictate the classification of glioma; instead, IDH status must be taken in conjunction with other prognostic mutations commonly found in gliomas in addition to the clinical and radiological status of the patient. This is reflected in the cIMPACT-NOW consortium guidelines (2018) which designate IDH-wildtype Grade II or III tumors, with one of the following molecular characteristics: EGFR amplification, or combined whole chromosome 7 gain and whole chromosome 10 loss, or TERT promoter mutation, as "diffuse astrocytic glioma, IDH-wildtype, with molecular features of glioblastoma, WHO grade IV."…”
Section: Exploring the Role Of Tumor Stratification Based On Idh Mutamentioning
confidence: 99%
“…34 A more recent meta-analysis by Vuong et al also demonstrated a propensity for IDH-wildtype low-grade gliomas to have a poor prognosis when associated with TERT promoter mutations, EGFR amplifications, and H3F3A mutations, whereas ATRX mutation, 7q gain/10q loss, and CDKN loss did not influence prognosis. 54 Thus, there is not enough evidence that IDH status alone should dictate the classification of glioma; instead, IDH status must be taken in conjunction with other prognostic mutations commonly found in gliomas in addition to the clinical and radiological status of the patient. This is reflected in the cIMPACT-NOW consortium guidelines (2018) which designate IDH-wildtype Grade II or III tumors, with one of the following molecular characteristics: EGFR amplification, or combined whole chromosome 7 gain and whole chromosome 10 loss, or TERT promoter mutation, as "diffuse astrocytic glioma, IDH-wildtype, with molecular features of glioblastoma, WHO grade IV."…”
Section: Exploring the Role Of Tumor Stratification Based On Idh Mutamentioning
confidence: 99%
“…The cIMPACT-NOW group addressed the molecular definition of 'molecular GBM', a cohort of IDH wild-type LGG characterized by either EGFR amplification, combined gains of chromosome 7 and loss of chromosome 10, or TERT promoter mutations [10]. A meta-analysis also assessed the prognostic values of several genetic markers and found that TERT promoter, H3F3A mutation, and EGFR amplification have a negative impact on survival of IDH wild-type LGG [11]. However, the transcriptional and biological heterogeneities within IDH wild-type diffuse LGGs need further dissection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HK2, fructose phosphate kinase, pyruvate kinase 2, and isocitrate dehydration may be prognostic biomarkers of multiple myeloma, prostate cancer, oral squamous cell carcinoma, and glioma. [22][23][24][25][26] This is because glucose metabolism enzymes have the ability to promote cancer migration, invasion, and angiogenesis. 27 Moreover, the characteristics of metabolic…”
Section: Discussionmentioning
confidence: 99%